2012
DOI: 10.21273/jashs.137.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Glycine Betaine Ameliorates the Adverse Effect of Salt Stress on Perennial Ryegrass

Abstract: Salinity stress may involve the accumulation of glycine betaine (GB). The objective of this study was to examine whether exogenous GB would ameliorate the detrimental effect of salinity stress on perennial ryegrass (Lolium perenne). The grass was subjected to two salinity levels (0 and 250 mm NaCl) and three GB levels (0, 20, and 50 mm). Salinity resulted in a remarkable decrease in vertical shoot growth rate (VSGR), shoot and root fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
78
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 54 publications
(65 reference statements)
15
78
0
1
Order By: Relevance
“…Our previous study had confirmed that the changes of macronutrient cations content, such as Ca 2+ , Mg 2+ , Na + , and K + , are necessary for salinity adaptation of perennial ryegrass12. In this study, NaCl treatment decreased K + but increased Na + concentration in leaves, stems and roots, which is consistent with our previous studies1231. In roots, external Ca 2+ application significantly increased K + concentration but decreased Na + concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study had confirmed that the changes of macronutrient cations content, such as Ca 2+ , Mg 2+ , Na + , and K + , are necessary for salinity adaptation of perennial ryegrass12. In this study, NaCl treatment decreased K + but increased Na + concentration in leaves, stems and roots, which is consistent with our previous studies1231. In roots, external Ca 2+ application significantly increased K + concentration but decreased Na + concentration.…”
Section: Discussionsupporting
confidence: 92%
“…A similar study conducted by Hu et al (2012) on Lolium perenne also confirmed the role of GB as a stress protectant. The plants were subjected to NaCl stress and application of GB to them significantly enhanced growth, relative water content, transpiration rate, pigment content, and activities of the antioxidative enzymes.…”
Section: Salinity Stresssupporting
confidence: 66%
“…Salinity stress may cause damage to plant physiological processes by over accumulation of reactive oxygen species (ROS), ion toxicity, impairment of antioxidant defense systems, photosynthetic function, and imbalance of hormones (Hu et al, 2012, 2015; Kim et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Proline severs as osmoprotentant and antioxidant to protect cells under salt stress. Salt stress may cause nutrient imbalance with increasing uptake of Na + and decreasing K + , Mg 2+ , and Ca 2+ , resulting in Na + toxicity (Hu et al, 2012; Gu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%